Fictions of the Island: girdling the sea. Issue 4 (December 2016) - Staley, Lynn
Abstract Like the sea, its highway, trade's fluctuation threatens attempts to fix value, demanding a narrative by which the restless and insatiable can appear domesticated. This essay explores late medieval texts that provide an imaginary of mercantile perspective during a crucial period of Britain's urban history. Through their depictions of the sea, they trace the growing power of merchant ideology, suggesting something of how merchants sought to create an identity for themselves within an existing social model, a model no more stable than the sea road of merchant ambition and endeavor. In so doing, the texts also offer ways in which the sea's indeterminacy was harnessed or made to appear so.